Recycle polystyrene as a binder of PCM-Impregnated particle board: effect of density - Aisha Adlina Azlam (2024)
This research investigates the environmental and thermal properties of wood composites produced using polystyrene resin as an adhesive and sawdust infused with palmitic acid as a phase change material (PCM). The composites were developed to explore their potential as eco-friendly alternatives in construction and thermal regulation applications. Utilizing rubber wood dust bound with polystyrene resin aimed to reduce environmental impact compared to conventional synthetic polymers. Furthermore, impregnating sawdust with palmitic acid aimed to enhance energy efficiency by leveraging the phase change capabilities of the acid. The findings imply that utilizing polystyrene resin as an adhesive and impregnating sawdust with PCM could yield environmentally friendly wood composites with enhanced thermal properties. These composites hold potential for applications in sustainable construction and energy-efficient building systems, contributing to reduced energy consumption and environmental mitigation. Further research is needed to explore optimization techniques and scale-up possibilities for practical implementation